Importancia de los factores climáticos en el desarrollo agronómico de los principales cultivos de ciclo corto en la provincia de Los Ríos” - Jiménez Zúñiga, Ninfa Marlene (2020)
The following research work, which is the practical component of the Complexive exam, has as its main objective to establish the importance of climatic factors in the agronomic development of the main short-cycle crops that are produced in the province of Los Ríos. They used the deductive and inductive methods, because the hypotheses were raised and tested throughout the development of the research in order to reach the conclusions and recommendations of the work. All the climatic factors involved in the agronomic development of the main short-cycle crops are described, in which the following were considered: rice, corn, soybeans and sorghum. In addition, the database used for the study of the different climatic factors that influence the short-cycle crops already mentioned, from which the necessary information was analyzed and extracted, was duly analyzed.